LEGAL PERSONALITY AS A GENERAL (ABSTRACT) LEGAL POSSIBILITY - Leyloyan, Hasmik (State and Law, 2024)
The philosophical-legal concepts of "legal possibility" and "legal reality" manifest themselves in specific ways in the existing structures of the functioning of one of the key categories of the general theory of law — legal personality, as well as in its components of legal capacity and legal capacity to act. In the process of identifying these manifestations and analyzing various types of legal possibilities, especially general (abstract) legal possibility, the author places the philosophical-legal category of "possibility" at the core of the concept of "legal personality". From this perspective, separately are considered legal capacity and legal capacity to act as general (abstract) legal possibilities, subjective rights as real legal possibilities, as well as the relationship between these categories is analyzed, highlighting their main differences and the necessity of differentiation. The author also draws special attention to the question of legal capacity (or legal personality) as a general (abstract) legal possibility of legal entities that are subjects of the law. According to the conclusion presented in the article, the analysis of legal personality as a general (abstract) legal possibility has important methodological significance, as it examines and identifies the legal prerequisites that enable a deep understanding of the structure of the effective realization of law and legislation, which is particularly important for lawmaking activities and law implementation practice.